Students' perceptions of computer-based learning environments, their attitude towards business statistics, and their academic achievement: implications from a UK university - Nguyen, ThuyUyen H.; Charity, Ian; Robson, Andrew (Studies in higher education (Dorchester-on-Thames), 2016)
This study investigates students' perceptions of computer-based learning environments, their attitude towards business statistics, and their academic achievement in higher education. Guided by learning environments concepts and attitudinal theory, a theoretical model was proposed with two instruments, one for measuring the learning environment and the other for measuring student attitude. Data were collected from 453 postgraduate business students in a UK university. Factor analyses were carried out to validate the instruments, whilst structural equation modelling was employed to validate the proposed model. The results demonstrate the importance of students' perceptions of subject integration within the learning environment and the relationship between their perceptions of cohesiveness, task orientation, and anxiety. The findings show that attitude towards statistics is significantly related to achievement, explaining almost 40% of variation, whilst perception of the learning environment (indirectly) explains about 29% of the achievement. Implications for teaching business statistics in higher education are discussed.